PENGARUH UKURAN PERUSAHAAN DAN KARAKTERISTIK KOMITE AUDIT TERHADAP AUDIT REPORT LAG DENGAN TENURE KAP SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2016-2020) - DWI HAYU ESTIRINI; Dian Prasetyo Widyaningtyas; Dini Vai Satria Manurung (Applied Research in Management and Business, 2022)
This research aims to determine the effect of company size and audit characteristics of committee audit to the acceptance of Audit Report Lag with tenure of public Accounting Firm’s as moderate variable. The samples of this research are mining sector companies which listed on the Indonesia Stock Exchange (BEI) in 2016 to 2020. The samples used as many as 85 companies with a purposive sampling technique and interaction test with the help of SmartPLS software. The result of this research show that company size is significant influence on audit report lag, hile audit characteristics of committee audit is no significant effect on the Audit Report Lag. And then after moderating show that that tenure of public Accounting Firm’s is moderating variable in the company size on auditreport lag whereas for tenure of public Accounting Firm’s is not moderating variable in the relationship characteristics of committee audit on audit report lag